Modelando el crecimiento individual de la ostra japonesa Crassostrea gigas cultivado en el Golfo de California mediante el modelo de von Bertalanffy - Góngora Gómez, Andrés Martín; Aragón Noriega, E. Alberto; Domínguez-Orozco, Ana Laura; Villanueva Fonseca, Brenda Paulina (Revista de Biología Marina y Oceanografía, 2019)
This study demonstrate the advantage of multi-model approach to calculate the growth of Crassostrea gigas cultivated in the Gulf of California. The generalized von Bertalanffy growth model (VBGM) and its modification to represent the seasonal variations (VBGM seasonal) were tested. The parameters of each model and their confidence intervals were computed using the maximum-likelihood method. The best-fitting model was selected using the Akaike information criterion (AIC). According to the AIC, the VBGM seasonal best described the growth of the C. gigas. The conclusion was that C. gigas exhibits a seasonal growth pattern under the cultivation conditions of the present study.